Option D
Using the distributive property, -7(8x – 3) + x = -55x + 21
Solution:
Given that we have to use distributive property to simplify the given expression
Given expression is:
-7(8x – 3) + x
Let us first understand about distributive property
The distributive property lets you multiply a sum by multiplying each addend separately and then add the products.
The distributive property is represented as:
a(b + c) = ab + ac
Apply this property in given expression for -7(8x - 3)
[tex]-7(8x - 3) = (- 7 \times 8x) + (-7 \times -3)\\\\-7(8x - 3) = -56x +21[/tex]
Apply the above result in given expression
[tex]-7(8x - 3) + x = -56x + 21 + x[/tex]
Combine the like terms. Add -56x and x
[tex]-7(8x - 3) + x = -56x + 21 + x = -55x + 21\\\\-7(8x - 3) + x = -55x + 21[/tex]
Thus the given expression is simplified. Option D is correct